Husker Du [interview with Grant Hart] (1986)
Interview with Grant Hart, songwriter, singer, and drummer for Husker Du, conducted by KCPR DJs Mike Stand and Rob Campanello. Songs and fragments of songs are interspersed with the interview content. [00:00:00] Intro, with Mike Stand and Rob Campanello. History of Husker Du, interspersed with a few of their songs [00:07:00] Phone interview with Grant Hart, drummer and singer, begins [00:08:39] (song plays) [00:11:00] Most important aspect of the band [00:11:40] (song plays) [00:15:40] Discussion of individual songs, and the voting process within the band [00:16:25] Grant Hart's songwriting process [00:16:45] Inspiration for Bob Mould, Husker D's other songwriter [00:17:00] (song plays) [00:19:00] Discussion of the song "Green Eyes" (and the song plays) [00:22:00] Discussion of the song "Flexible Flyer" (and the song plays) [00:26:40] Discussion of the New Day Rising LP and the song "Books About UFOs" (and the song plays) [00:30:35] Content of songs: relationships, emotions (song plays) [00:34:17] (song plays) [00:36:35] Discussion of Zen Arcade album as a concept album [00:38:12] (song "Pink Turns to Blue" plays) [00:40:56] Discussion of whether Husker Du's sound will change after switch to major label [00:41:53] (song "Turn on the News" plays) [00:46:23] Discussion of whether Husker Du will record more acoustic songs [00:46:40] (song plays) [00:48:27] Discussion of the experience of being on a major label and playing concerts with bigger crowds [00:49:04] (song plays) [00:52:44] On being called a sell out [00:53:56] Grant Hart station ID [00:54:05] (song plays) [00:59:06] End credits